2012
DOI: 10.1097/aog.0b013e318240de51
|View full text |Cite
|
Sign up to set email alerts
|

Nodal Metastasis Risk in Endometrioid Endometrial Cancer

Abstract: Objective To estimate the risk for nodal metastasis in women with endometrial cancer based on uterine characteristics on pathology. Methods From a study of staging for uterine cancer, women were identified as low risk for nodal metastasis based on three specific criteria on final pathology reports: 1) less than 50% invasion; 2) tumor size less than 2 cm; and 3) well or moderately differentiated endometrioid histology. If the uterine specimen did not meet all three criteria, it was viewed as high risk for nod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
89
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 146 publications
(95 citation statements)
references
References 22 publications
3
89
0
2
Order By: Relevance
“…On the other hand, Mariani et al reported that lymphadenectomy can be omitted under the following conditions: endometrioid histology (grade 1 or 2), myometrial invasion b 50%, and tumor diameter b 2 cm [7]. Gynecologic oncologists in the United States regard these three factors as being important and have named them "Mayo criteria" [8]. A unique point of the Mayo criteria is that tumor size is used together with myometrial invasion.…”
Section: Introductionmentioning
confidence: 98%
“…On the other hand, Mariani et al reported that lymphadenectomy can be omitted under the following conditions: endometrioid histology (grade 1 or 2), myometrial invasion b 50%, and tumor diameter b 2 cm [7]. Gynecologic oncologists in the United States regard these three factors as being important and have named them "Mayo criteria" [8]. A unique point of the Mayo criteria is that tumor size is used together with myometrial invasion.…”
Section: Introductionmentioning
confidence: 98%
“…Nonetheless, a wide range of intraoperative treatment options including comprehensive lymphadenectomy, selective lymphadenectomy or no staging at all exists. In the study of 970 women with EC, Milam et al estimated less than 1% risk of nodal metastasis in Mayo clinic low risk EC patients [19]. Therefore, there is a general consensus among many gynecologic oncologists not to perform comprehensive lymphadenectomy for the Mayo Clinic low risk patients with EC.…”
Section: Discussionmentioning
confidence: 98%
“…Several authors have proposed different scores in order to predict LN metastasis [45][46][47][48][49][50][51][52][53] (table 2).…”
Section: Scores To Predict Ln Metastasismentioning
confidence: 99%